4. a) 2(x + 3) - 3(x - 1) = 3x - 2(2 + x)
2x + 6 - 3x + 3 = 3x - 4 - 2x
-x + 9 = x - 4
-x - x = -4 - 9
-2x = -13
x = 13 / 2
b) (x + 2) ² + 3(x - 2) = (x + 1) (x - 1) - 8
x² + 4x + 4 + 3x - 6 = x² - x + x - 1 - 8
x² + 7x - 2 = x² - 9
x² - x² + 7x = -9 + 2
7x = -7
x = -1
5. a) (2x + 3)² - 2(x - 1)(x + 1) + 15 = 3(2 - x)² - (x + 1)² - 11
4x² + 12x + 9 - 2(x² + x - x - 1) + 15 = 3(4 - 4x + x²) - (x² - 2x + 1) - 11
4x² + 12x + 9 - 2x² + 2 + 15 = 12 - 12x + 3x² - x² + 2x - 1 - 11
2x² + 12x + 26 = 2x² - 10x
12x + 10x = -26
22x = -26
x = - 13 / 11